Elevated glucose levels in early puerperium, and association with high cortisol levels during parturition. (18th May 2016) - Risberg, Anitha; Sjöquist, Mats; Wedenberg, Kaj; Larsson, Anders
Abstract: Background Gestational diabetes is one of the commonest metabolic problems associated with pregnancy and an accurate diagnosis is critical for the care. Research has shown that pregnant women have high levels of cortisol during the last stage of parturition. As cortisol is a diabetogenic hormone causing increased glucose levels, we wanted to study the association between cortisol and glucose levels during parturition.Materials and methods Glucose and cortisol were analyzed during parturition in 50 females divided according to slow ( n = 11) and normal labors ( n = 39). Blood samples were analyzed three times during the parturition and four times in the first day after delivery. Glucose levels were also measured once in each trimester.Results In the normal group, the glucose concentration increased from 6.2 (IQR 5.6–8.0) mmol/L in the latency phase to 11.6 (10.0–13.3) mmol/L at aftercare ( p < 0.05). After parturition the glucose concentrations decreased gradually. There were significant Spearman rank correlations between glucose and cortisol values.Conclusions The changes associated with birth cause significant elevations of cortisol and glucose around parturition.